The Effect of Ulva lactuta Polysaccharide Extract on Total Haemocyte Count and Phagocytic Activity of L. vannamei - Suleman Suleman; Sri Andayani; Ating Yuniarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
This research aimed to evaluate the effect of polysaccharide extract of Ulva lactuta on the total haemocytes count (THC) and the phagocytic activities (PA) on Litopenaeus vannamei. The concentration of the extract used in this research was 5 ppm and it was applied through the immersion. The haemolymph was collected after the administration in the different periods at hour of 4 and 24. The results showed that the administration of polysaccharide extracts increased THC and PA in L. vannamei significantly (p<0.05). THC and PA of white-leg shrimp with polysaccharide extract was higher than that without the administration of the extract. The enhancement of THC was found after the administration at hour 4 from 5.00 cells. ml-1 to 5.26 x 104 cells. ml-1. However, the THC level decreased after 24 hours at the value of 5.19 x 104 cells. The increasing pattern was also true for PA of L. vannamei, from 40.44% to 53.67% (hour 4). At the hour of 24, the PA was found decreased to the level and then decreased 45.67 ±1.53. On the contrary, there were no enhancement of THC and PA in the treatment without polysaccharide extract of Ulva lactuta.